Constitutive expression of HCA(2) in human retina and primary human retinal pigment epithelial cells - Yu, Alice L.; Birke, Kerstin; Lorenz, Reinhard L.; Welge-Lüssen, Ulrich-Christoph (Current Eye Research, 2014)
HCA2, a receptor of ?-hydroxybutyrate and niacin, has recently been described in mouse retina and immortalized human retinal pigment epithelial (RPE) cell lines. As HCA2 might be a pharmacologic target, e.g. in diabetic retinopathy, we studied its expression in human retina and primary human RPE cells.Paraffin sections of human retina and primary human RPE cells were obtained from human donor eyes. Expression of HCA2 in human retina was investigated by immunohistochemistry of paraffin sections and by RT-PCR. HCA2 expression in primary human RPE cells was examined by immunocytochemistry and by Western-blot analysis.Positive immunohistochemical staining for HCA2 was found in paraffin sections of human retina, and positive immunocytochemical staining for HCA2 in primary human RPE cells. RT-PCR analysis detected mRNA expression of HCA2 in human retina. The expression of HCA2 protein was found in primary human RPE cells.Based on these results, HCA2 appears to be constitutively expressed in human retina and in primary human RPE cells. Although its functional role is still unknown, HCA2 may be potentially involved in the pathogenesis of various retinopathies and may offer a new therapeutic target.
EVALuna2:21027